Extracellular Signal-Regulated Kinase-Regulated Microglia–Neuron Signaling by Prostaglandin E(2) Contributes to Pain after Spinal Cord Injury - Zhao, Peng (J Neurosci, 2007)
Many patients with traumatic spinal cord injury (SCI) report pain that persists indefinitely and is resistant to available therapeutic approaches. We recently showed that microglia become activated after experimental SCI and dynamically maintain hyperresponsiveness of spinal cord nociceptive neurons and pain-related behaviors. Mechanisms of signaling between microglia and neurons that help to maintain abnormal pain processing are unknown. In this study, adult male Sprague Dawley rats underwent T9 spinal cord contusion injury. Four weeks after injury when lumbar dorsal horn multireceptive neurons became hyperresponsive and when behavioral nociceptive thresholds to mechanical and thermal stimuli were decreased, we tested the hypothesis that prostaglandin E(2) (PGE(2)) contributes to signaling between microglia and neurons. Immunohistochemical data showed specific localization of phosphorylated extracellular signal-regulated kinase 1/2 (pERK1/2), an upstream regulator of PGE(2) release, to microglial cells and a neuronal localization of the PGE(2) receptor E-prostanoid 2 (EP2). Enzyme immunoassay analysis showed that PGE(2) release was dependent on microglial activation and ERK1/2 phosphorylation. Pharmacological antagonism of PGE(2) release was achieved with the mitogen-activated protein kinase kinase 1/2 (MEK1/2) inhibitor PD98059 [2-(2-amino-3-methyoxyphenyl)-4H-1-benzopyran-4-one] and the microglial inhibitor minocycline. Cyclooxygenase-2 expression in microglia was similarly reduced by MEK1/2 inhibition. PD98059 and EP2 receptor blockade with AH6809 (6-isopropoxy-9-oxoxanthene-2-carboxylic acid) resulted in a decrease in hyperresponsiveness of dorsal horn neurons and partial restoration of behavioral nociceptive thresholds. Selective targeting of dorsal horn microglia with the Mac-1–synapse-associated protein (SAP) immunotoxin resulted in reduced microglia staining, reduction in PGE(2) levels, and reversed pain-related behaviors. On the basis of these observations, we propose a PGE(2)-dependent, ERK1/2-regulated microglia–neuron signaling pathway that mediates the microglial component of pain maintenance after injury to the spinal cord.